Effect of Al Content on Magnetic Properties and Thermal Expansion of As-Cast High-Entropy Alloys AlxFeCoNiCuCr - Nadutov, V.M.; Makarenko, S.Yu.; Svystunov, Ye.O. (Металлофизика и новейшие технологии, 2015)
The high-entropy alloys (HEA) AlxFeCoNiCuCr (x = 1.0, 1.5, 1.8) in cast state are investigated by means of X-ray diffraction, Mössbauer spectroscopy, magnetic and dilatometric methods. Two-phase state in the HEA and the increase of the crystal lattice parameter а of the f.c.c. and b.c.c. phases are detected. The decrease of the Curie temperature and the saturation magnetization upon deviation of Al content from equimolar composition are found out. Inhomogeneous magnetic order characterizes the studied HEA. For the studied HEA, the magnetic moment 0.2—0.4 μB and the average thermal expansion coefficient <α> = 12.4∙10⁻⁶ К⁻¹ in the temperature range of 135—545 K are determined.